Repeated Bout Effect of Two Resistance Training Bouts on Bowling-Specific Performance in Male Cricketers - Drew C. Harrison; Kenji Doma; Anthony S. Leicht; Teneale A. McGuckin; Carl T. Woods; Jonathan D. Connor (MDPI AG, 2022)
To examine the repeated bout effect (RBE) following two identical resistance bouts and its effect on bowling-specific performance in male cricketers. Male cricket pace bowlers (N = 10), who had not undertaken resistance exercises in the past six months, were invited to complete a familiarisation and resistance maximum testing, before participating in the study protocol. The study protocol involved the collection of muscle damage markers, a battery of anaerobic (jump and sprint), and a bowling-specific performance test at baseline, followed by a resistance training bout, and a retest of physical and bowling-specific performance at 24 h (T24) and 48 h (T48) post-training. The study protocol was repeated 7-10 days thereafter. Indirect markers of muscle damage were lower (creatine kinase: 318.7 ± 164.3 U·L−1; muscle soreness: 3 ± 1), whilst drop jump was improved (~47.5 ± 8.1 cm) following the second resistance training bout when compared to the first resistance training bout (creatine kinase: 550.9 ± 242.3 U·L−1; muscle soreness: 4 ± 2; drop jump: ~43.0 ± 9.7 cm). However, sport-specific performance via bowling speed declined (Bout 1: −2.55 ± 3.43%; Bout 2: 2.67 ± 2.41%) whilst run-up time increased (2.34 ± 3.61%; Bout 2: 3.84 ± 4.06%) after each bout of resistance training. Findings suggest that while an initial resistance training bout reduced muscle damage indicators and improved drop jump performance following a second resistance training bout, this RBE trend was not observed for bowling-specific performance. It was suggested that pace bowlers with limited exposure to resistance training should minimise bowling-specific practice for 1-2 days following the initial bouts of their resistance training program.